PENERAPAN PEMBAYARAN QRIS UNTUK MENINGKATKAN TRANSPARANSI PENGELOLAAN KEUANGAN UMKM DI KOTA GORONTALO - Hasanani, Edo Setiawan; Mopangga, Herwin; Bumulo, Frahmawati (Jurnal Studi Ekonomi dan Pembangunan, 2024)
This research aims to find out how to increase the transparency of financial management of Micro, Small and Medium Enterprises (MSMEs) in Gorontalo City. This research is a qualitative descriptive research that conducts an assessment of how changes in the income and financial management of their MSMEs. The sample in this study is MSME actors in Gorontalo City who use QRIS. The results of this study show that QRIS is able to improve the financial management of MSME actors in Gorontalo City and the income of MSME actors is also about changes even if it is small. The existence of this non-cash payment method on average is very helpful for the transparency of financial management of MSME actors in Gorontalo City, where previously their financial management was not very regular. Keywords: MSMEs; QRIS; Transparency.